Ergonomic interventions to improve musculoskeletal disorders among vehicle assembly workers: a one-year longitudinal study - Xu Jin; Yidan Dong; Longao Yang; Wenchu Huang; Lei Cao; Zhongbin Zhang; Lihua He (BMC Public Health)
Abstract Background Musculoskeletal disorders (MSDs) constitute a significant challenge in the realm of occupational health, especially in the manufacturing sector, necessitating the development of efficacious intervention strategies to enhance musculoskeletal health and reduce the incidence of MSDs. The present study is designed to assess the efficacy of a comprehensive ergonomic intervention, specifically tailored to diminish ergonomic risk factors and the prevalence of MSDs among workers engaged in vehicle assembly line operations. Method This interventional study, conducted over a one-year period, was implemented among assembly line workers within a rail bound vehicle manufacturing shop. The study engaged 181 participants who were subjected to a comprehensive ergonomic intervention plan. This intervention encompassed an ergonomic training program, enhancements in auxiliary tool, and the distribution of an ergonomic educational brochure. Workstation ergonomics, including postures and movements, vibrations, and work stress, were evaluated using the Quick Exposure Check (QEC). Participants scored their postural exposure and the intensity, duration, and frequency of musculoskeletal symptoms at nine anatomical sites in the modified Nordic Musculoskeletal Questionnaire. All evaluations were conducted at baseline and after a one-year follow-up. Results After the one-year intervention, the QEC scores for the neck, back, shoulders/arms, and wrists/hands decreased significantly (p < 0.01). The self-rated exposure scores for 22 awkward postures and repetitive movements were much lower than at baseline (p < 0.05). Moreover, the self-reported intensity, duration, and frequency of musculoskeletal symptoms in nine body areas all decreased significantly (p < 0.05). Conclusions The findings from this prospective study indicated enhancements in ergonomic conditions and a reduction in musculoskeletal disorders (MSDs) among vehicle assembly workers following a comprehensive ergonomic intervention.